Hybrid manufacturing and mechanics of architected interpenetrating phase composites: review and perspectives - Qinze Song; Agyapal Singh; Nikolaos Karathanasopoulos (Virtual and Physical Prototyping)
Characterized by their unique topological and mechanical metrics, interpenetrating phase composites (IPCs) have emerged as a versatile class of materials with advanced performance, garnering significant interest across academia and industry. This work comprehensively investigates the manufacturing methods and mechanical properties of IPCs, with a focus on metal-metal, ceramic-metal, polymer-metal, and polymer-ceramic architected interpenetrating phase designs. The state-of-the-art hybrid techniques typically employed in their manufacturing are critically examined-including additive manufacturing, casting, electrodeposition, and dealloying processes-highlighting their similarities, novelties, and limitations associated with each co-continuous composite class. A large body of experimental data is collected and comparatively analysed, summarising primal physical metrics. The inner design is associated with the arising effective mechanical performance, comparatively quantifying Young's moduli, yield and ultimate strengths, critical densification or fracture strains, and specific energy absorptions. The extended datasets form the basis for the creation of comprehensive Ashby plot representations of the aforementioned performance metrics, offering unique insights into their mechanical performance. As such, this work provides a foundational understanding of the IPC manufacturing processes and resulting mechanics, identifying gaps in current knowledge and suggesting avenues for future exploration in this rapidly evolving field.